CONTROL ON THE FREE BOUNDARY OF A VISCOELASTIC BEAN WITH MEMORY - Santiago Ayala, Yolanda Silvia (2009)
Using Semigroups Theory, we prove the existence of global solution to the viscoelastic bean equation with memory, this bean is having one side fixed and the other one is provided of a control ƒ. Also, using multiplication techniques, Lyapunov functional, dynamic systems and some results of Datko, Buck, we show that the energy associated to the system decays to zero when t → + ∞, that means we get the stability of the bean.